Extrusion deposition 3D printed PCL/gel/n-HA composite scaffold for bone regeneration. Issue 9 (13th June 2023) - Wang, Chenxin; Liu, Jie; Lin, Mingyue; Zhang, Rui; Li, Yufan; Li, Yubao; Zou, Qin
Abstract: In this study, we aimed to improve the hydrophilicity, cellular activities and osteogenesis of polycaprolactone (PCL) scaffolds by adding gelatin (Gel) and nano-hydroxyapatite (n-HA). We fabricated biocomposite scaffolds using the extrusion deposition 3 D printing method. The physical and biological properties of the composite scaffold were evaluated. Scanning electron microscopy (SEM) of the fabricated composite scaffolds revealed that the Gel and n-HA particles were uniformly embedded in the internal PCL. The composite scaffold (PCL + Gel + n-HA) showed dramatically improved mechanical properties. The porosity, hydrophilicity and hydrophobicity and ability to promote the attachment and proliferation of osteoblasts were then compared between the pure PCL and composite scaffolds. The PCL + Gel + n-HA scaffold was implanted in the rabbits for 5 weeks, and the results of H&E and Masson staining analyses demonstrated that the scaffold had good biocompatibility and good osteogenesis. The strategy developed in this study has promising prospects for future clinical applications of enhancing bone defect repair. Graphical Abstract: UF0001